Polyvinyl alcohol film, polarizing film and polarizing plate
By adding an acid capture agent to the polyvinyl alcohol film, the problem of the polarizing plate reducing light transmittance in the high temperature environment in the prior art is solved, and higher durability is achieved.
Patent Information
- Application Number
- CN202080021119.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-14
- Filing Date
- 2020-03-10
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-03-10
AI Technical Summary
The prior art cannot sufficiently suppress the decrease in the light transmittance of the polarizing plate under a high temperature environment of 105°C or above, resulting in insufficient durability of the liquid crystal display.
Polyeneization of the polarizing film is inhibited by adding an acid capture agent, especially a compound having a carbodiimide group, to the polyvinyl alcohol film, so that the light transmittance is stable under high temperature conditions.
It effectively suppresses the reduction of the light transmittance of the polarizing plate and improves the durability of the liquid crystal display in high temperature environments.
Smart Images

Figure CN113544555B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polyvinyl alcohol film, a polarizing film and a polarizing plate. Background Art
[0002] Polarizing plates, which have light-transmitting and light-shielding functions, are the basic components of liquid crystal displays (LCDs) along with liquid crystals that change the polarization state of light. Many polarizing plates have a structure in which a protective film such as a triacetylcellulose (TAC) film is attached to the surface of the polarizing film. The polarizing film constituting the polarizing plate is a stretched film obtained by uniaxially stretching a polyvinyl alcohol film (hereinafter sometimes referred to as "PVA") to orient it, and an iodine-based dye (I3 - 、I5 - Polarizing films with dichroic pigments such as polyvinyl alcohol (PVA), ...
[0003] LCDs are increasingly being used in small devices such as calculators and watches, notebook personal computers, LCD TVs, mobile phones, tablet terminals, etc. In recent years, LCDs are also being used as in-vehicle image display devices such as car navigation devices and reversing monitors. As a result, LCDs are being required to have higher durability in harsher environments than ever before.
[0004] It is known that when an image display device formed by laminating a polarizing plate between an image display unit and a transparent plate such as a front panel or a touch panel via an adhesive layer is subjected to a long-term high-temperature durability test required for an in-vehicle display, the light transmittance of the polarizing plate decreases. One reason for this is the polyeneization of PVA constituting the polarizing film, and the higher the temperature, the more significant the decrease in the light transmittance of the polarizing plate.
[0005] Regarding the polyene problem of such polarizing plates, Patent Document 1 states that polyene can be suppressed by using a polarizing plate having a protective film with high moisture permeability on the surface of the polarizing film. Patent Document 2 states that polyene can be suppressed by adjusting the thickness of the adhesive used to bond the polarizing plate to the image display unit and the transparent plate, and the absorbance of the polarizing film.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2014-102353
[0009] Patent document 2: Japanese Patent Application Publication No. 2018-25764. Summary of the invention
[0010] Problem that the invention aims to solve
[0011] However, according to the inventors' research, although the methods described in Patent Documents 1 and 2 tend to suppress the decrease in light transmittance of polarizing plates, sufficient polyene-inhibiting effects were not confirmed in durability tests in high-temperature environments of 105° C. or higher, which are required in recent years.
[0012] The present invention is based on the above situation, and its purpose is to provide a PVA film capable of manufacturing a polarizing film, a polarizing film obtained using such a PVA film, and a polarizing plate obtained using the polarizing film, wherein the polarizing film can fully suppress the reduction in light transmittance of the polarizing plate in a high-temperature durability test.
[0013] Methods used to solve problems
[0014] The inventors of the present invention have repeatedly conducted in-depth studies to achieve the above-mentioned purpose, and as a result, found that the polyeneization of PVA in the polarizing film of the polarizing plate is promoted by the acid generated by the protective film, and that the polyeneization is inhibited by giving the polarizing film or the PVA film serving as the original film of the polarizing film a function of capturing acid. Based on these insights, further repeated studies were conducted to complete the present invention.
[0015] That is, the present invention relates to the following:
[0016] [1] A polyvinyl alcohol film comprising polyvinyl alcohol, wherein the absorbance A1 and the average thickness D1 (mm) of the polyvinyl alcohol film at a wavelength of 210 nm satisfy the following formula (1);
[0017] A1 / D1≥9 ・・・(1)
[0018] [2] The polyvinyl alcohol film according to [1], wherein the absorbance A1 and the average thickness D1 (mm) satisfy the following formula (2);
[0019] 9≤A1 / D1≤80 ・・・(2)
[0020] [3] The polyvinyl alcohol film according to [1] or [2], comprising an acid scavenger;
[0021] [4] A polyvinyl alcohol film comprising polyvinyl alcohol and an acid scavenger, wherein the content of the acid scavenger is 0.1 parts by mass or more relative to 100 parts by mass of the polyvinyl alcohol;
[0022] [5] The polyvinyl alcohol film according to [3] or [4], wherein the acid scavenger is an organic compound;
[0023] [6] The polyvinyl alcohol film according to [5], wherein the acid scavenger is a carbodiimide compound having at least one carbodiimide group.
[0024] [7] The polyvinyl alcohol film according to any one of [3] to [6], wherein the acid scavenger is water-soluble;
[0025] [8] The polyvinyl alcohol film according to [7], wherein the acid scavenger is a polymer;
[0026] [9] The polyvinyl alcohol film according to any one of [1] to [8], wherein the saponification degree of the polyvinyl alcohol is 90 mol% or more;
[0027]
[10] The polyvinyl alcohol film according to any one of [1] to [9], which is used for manufacturing a polarizing plate;
[0028]
[11] A polarizing film formed from the polyvinyl alcohol film according to any one of [1] to
[10] ;
[0029]
[12] A polarizing film containing polyvinyl alcohol, wherein the absorbance A2 at a wavelength of 210 nm after standing for 100 hours in an atmosphere of 60 °C and 90% RH and the average thickness D2 (mm) satisfy the following formula (3);
[0030] A2 / D2 ≥ 9 ··· (3)
[0031]
[13] A polarizing plate having the polarizing film of
[11] or
[12] and a protective film containing a cellulose ester resin.
[0032] Effects of the Invention
[0033] According to the present invention, a PVA film capable of manufacturing a polarizing film, a polarizing film obtained by using such a PVA film, and a polarizing plate obtained by using the polarizing film can be provided, and the polarizing film can sufficiently suppress a decrease in the light transmittance of the polarizing plate in a high-temperature durability test. Description of the Drawings
[0034] Figure 1 Absorption spectra of the PVA films of Examples 1 to 3 and Comparative Example 1. Detailed Description of the Invention
[0035] Hereinafter, embodiments of the present invention will be described in detail.
[0036] <PVA Film>
[0037] The PVA film according to one embodiment of the present invention is a PVA film containing PVA, and the absorbance A1 at a wavelength of 210 nm and the average thickness D1 (mm) satisfy the following formula (1).
[0038] A1 / D1≥9 ・・・(1)
[0039] Here, the average thickness D1 of the PVA film refers to the average value of the values measured at any 10 locations. The same applies to the average thickness of the film below. In addition, the unit of A1 / D1 is mm -1 .
[0040] The absorption at a wavelength of 210 nm is due to the absorption of the groups that can capture acid. As shown in Comparative Example 1 described later, the PVA film without the addition of a component having a group that can capture acid also has a certain degree of absorption near the wavelength of 210 nm, and the value of A1 / D1 reaches 8 mm. -1 About (refer to Table 1, Figure 1 ). In contrast, by adding a component having a group capable of capturing acid, the absorption near a wavelength of 210 nm becomes larger (refer to Figure 1 Examples 1 to 3, etc.). In the PVA film, there are a large number of groups that can capture acid, and the value of A1 / D1 reaches 9 mm -1 When the above is true, that is, when the PVA film satisfies the above formula (1), the PVA film can fully capture the acid. On the other hand, when a polarizing plate having a polarizing membrane and a protective film containing cellulose ester is exposed to high temperature for a long time, the cellulose ester constituting the protective film generates acid due to hydrolysis, etc., and the polarizing membrane is a stretched PVA membrane. It can be inferred that the acid becomes a catalyst for the dehydration reaction of PVA, and PVA undergoes polyeneization. In contrast, in a polarizing plate having a polarizing membrane obtained by using a PVA membrane satisfying formula (1), the acid generated by the protective film will be captured by the acid-capturing group present in the polarizing membrane, thereby suppressing the polyeneization of the PVA in the polarizing membrane in the polarizing plate. That is, based on this PVA film, a polarizing membrane can be manufactured that can fully suppress the reduction in light transmittance of the polarizing plate in a high-temperature durability test.
[0041] As a group that can capture acid and has absorption at a wavelength of 210nm, a carbodiimide group (-N=C=N-) can be cited. The PVA film described in one embodiment of the present invention may contain a compound (acid scavenger) having a carbodiimide group, or a PVA having a carbodiimide group may be used, preferably containing an acid scavenger. The compound (acid scavenger) having a carbodiimide group usually has a maximum absorption near a wavelength of 210nm. The PVA film described in one embodiment of the present invention can show absorption at a wavelength of 210nm derived from the acid scavenger. The PVA film described in one embodiment of the present invention may have an acid scavenger with a maximum absorption near a wavelength of 210nm. In addition, the PVA film described in one embodiment of the present invention may be a substantially transparent film. The specific form of the acid scavenger is described in detail later. As a substantially transparent film, the absorbance in the entire range of wavelengths of 360nm~780nm is preferably less than 0.2, and more preferably less than 0.1.
[0042] Regarding the relationship between the absorbance A1 and the average thickness D1, the lower limit of A1 / D1 is preferably 10 mm. -1 , more preferably 12 mm -1 , more preferably 14 mm -1 , and more preferably 20 mm -1 , particularly preferably 25 mm -1 By setting A1 / D1 to be above the above lower limit, the acid capture capacity can be further improved, the polyene inhibition function can be fully exerted in the high temperature durability test, and a polarizing film that can more fully inhibit the decrease in the light transmittance of the polarizing plate can be manufactured. On the other hand, the upper limit of A1 / D1 can be, for example, 100 mm -1 , preferably 80mm -1 , more preferably 50 mm -1 By setting A1 / D1 to be less than or equal to the upper limit, the film surface becomes good, and the polarization performance of the obtained polarizing film can be improved. In the PVA film according to one embodiment of the present invention, the absorbance A1 and the average thickness D1 (mm) preferably satisfy the following formula (2).
[0043] 9≤A1 / D1≤80 ・・・(2)
[0044] The above A1 / D1 depends on the amount of the group having absorption at a wavelength of 210 nm. For example, the value of A1 / D1 can be adjusted by the amount of the compound having a group having absorption at a wavelength of 210 nm, that is, a carbodiimide group.
[0045] (PVA)
[0046] PVA is a polymer having a vinyl alcohol unit (-CH2-CH(OH)-) as a main structural unit. In addition to the vinyl alcohol unit, PVA may also have a vinyl ester unit or other units.
[0047] As PVA, PVA obtained by saponifying polyvinyl ester obtained by polymerizing one or more vinyl esters can be used. Examples of vinyl esters include vinyl acetate, vinyl formate, vinyl propionate, vinyl butyrate, vinyl pivalate, vinyl versatate, vinyl laurate, vinyl stearate, vinyl benzoate, isopropenyl acetate, and the like. Among the vinyl esters, compounds having a vinyloxycarbonyl group (H2C=CH-O-CO-) in the molecule are preferred from the viewpoints of ease of manufacture, ease of acquisition, and cost, and vinyl acetate is more preferred.
[0048] The polyvinyl ester is preferably an ester obtained by using only one or more vinyl esters as monomers, and more preferably a polyvinyl ester obtained by using only one vinyl ester as a monomer. As long as the effect of the present invention is not significantly impaired, it may be a copolymer resin formed by one or more vinyl esters and other monomers copolymerizable therewith.
[0049] The upper limit of the ratio of the structural unit derived from other copolymerizable monomers is preferably 15 mol %, more preferably 10 mol %, further preferably 5 mol %, and further preferably 1 mol % based on the number of moles of all structural units constituting PVA.
[0050] Examples of other monomers copolymerizable with the vinyl ester include α-olefins having 2 to 30 carbon atoms, such as ethylene, propylene, 1-butene, and isobutylene; (meth)acrylic acid or its salts; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate; (meth)acrylamide; N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, diacetone (meth)acrylamide, (meth)acrylamide propanesulfonic acid or its salts, (meth) ) (meth)acrylamide derivatives such as acrylamidopropyldimethylamine or its salts, N-hydroxymethyl (meth)acrylamide or its derivatives; N-vinylamides such as N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; vinyl cyanide such as (meth)acrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or its salts, esters or anhydrides; itaconic acid or its salts, esters or anhydrides; vinyl silyl compounds such as vinyltrimethoxysilane; unsaturated sulfonic acids or their salts, etc.
[0051] The polyvinyl ester may have a structural unit derived from one or two or more of the above-mentioned monomers.
[0052] As PVA, PVA that has not been graft copolymerized can be preferably used. Among them, PVA can be modified using one or more graft copolymerizable monomers. At least one of polyvinyl ester and PVA obtained by saponifying it can be graft copolymerized. Examples of graft copolymerizable monomers include unsaturated carboxylic acids or derivatives thereof; unsaturated sulfonic acids or derivatives thereof; α-olefins having 2 to 30 carbon atoms, etc. The proportion of structural units derived from graft copolymerizable monomers in polyvinyl ester or PVA is preferably 5 mol% or less based on the molar number of all structural units constituting polyvinyl ester or PVA.
[0053] Some of the hydroxyl groups in PVA may be cross-linked or not cross-linked. In addition, some of the hydroxyl groups in PVA may react with aldehyde compounds such as acetaldehyde and butyraldehyde to form acetal structures.
[0054] The lower limit of the degree of polymerization of PVA is preferably 1,000, more preferably 1,500, and further preferably 1,700. By making the degree of polymerization of PVA above the above lower limit, the softness of the PVA film can be improved. On the other hand, as the upper limit of the degree of polymerization, it is preferably 10,000, more preferably 8,000, and further preferably 5,000. By making the degree of polymerization of PVA below the above upper limit, the increase in the manufacturing cost of PVA and the occurrence of defects during film making can be suppressed. It should be noted that the degree of polymerization of PVA refers to the average degree of polymerization measured in accordance with the description of JIS K6726-1994.
[0055] From the perspective of good moisture and heat resistance of the obtained polarizing film, the saponification degree of PVA is preferably 90 mol% or more, more preferably 95 mol% or more, further preferably 99 mol% or more, and particularly preferably 99.5 mol% or more. The upper limit of the saponification degree is not particularly limited, and can be 100 mol% or 99.99 mol%. The saponification degree of PVA refers to the ratio (mol%) of the number of moles of vinyl alcohol units to the total number of moles of structural units (typically vinyl ester units) that can be converted into vinyl alcohol units by saponification and vinyl alcohol units. The saponification degree can be measured according to the description of JIS K6726-1994.
[0056] The lower limit of the content of PVA in the PVA film as one embodiment of the present invention is preferably 50% by mass, more preferably 80% by mass, and further preferably 85% by mass. By setting the content of PVA to be above the above lower limit, a good polarizing film can be obtained. On the other hand, the upper limit of the content of PVA is preferably 99% by mass, more preferably 95% by mass.
[0057] (Acid scavenger)
[0058] The suitable component of the PVA film described in one embodiment of the present invention, i.e., the acid scavenger, is a compound that reacts with an acid to deactivate the acid. As the acid scavenger, for example, organic compounds such as compounds having a carbodiimide group, compounds having an epoxy group, compounds having an oxazoline group, alkyl phosphate metal salts, strongly basic amino compounds, terpene compounds, oxazine compounds, and inorganic compounds such as hydrotalcites can be listed. Organic compounds refer to carbon-containing compounds, and inorganic compounds refer to compounds other than organic compounds. It should be noted that acid scavengers are sometimes also referred to as acid scavengers, acid scavengers, acid traps, etc., but in the present invention, these names are not different and can be used. Acid scavengers can be used alone or in combination of two or more.
[0059] The acid scavenger is preferably an organic compound. By using an organic compound as the acid scavenger, when the PVA film is stretched in the polarizing film manufacturing process, the acid scavenger is easily deformed along the stretching direction together with the PVA. Therefore, it is difficult to generate defects such as pores in the obtained polarizing film, and the polarization performance of the obtained polarizing film is improved.
[0060] Among the acid scavengers, carbodiimide compounds having at least one carbodiimide group are more preferred. Carbodiimide compounds are also preferred from the viewpoints of significant effect of suppressing polyene formation and ease of handling and safety.
[0061] The mass (molecular weight) of the acid scavenger per 1 mol of the group capable of scavenging an acid is preferably, for example, 200 g / mol or more and 1,000 g / mol or less. When the acid scavenger is a carbodiimide compound, the mass (molecular weight) of the group capable of scavenging an acid per 1 mol is also called a carbodiimide group equivalent, which is the mass per 1 mol of the carbodiimide group.
[0062] The acid scavenger is preferably water-soluble. By using a water-soluble acid scavenger that is easily compatible with PVA, a PVA film with high light transmittance, low haze, good film surface, and a polarizing film with good polarization performance can be obtained. It should be noted that "water-soluble" means that the solubility relative to water is 1g / water 100g or more. The solubility relative to water refers to the limit amount (mass) that dissolves in 100g of water at 20°C. As the lower limit of the solubility of the acid scavenger relative to water, it is preferably 2g / water 100g, and more preferably 3g / water 100g. By setting the solubility relative to water to above the above lower limit, the acid scavenger is more easily compatible with PVA, so that the film surface of the obtained PVA film and polarizing film is good, and the polarization performance of the polarizing film can be improved. On the other hand, as the upper limit of the solubility, for example, it can be 200g / water 100g, sometimes preferably 100g / water 100g, more preferably 50g / water 100g, 20g / water 100g, and further preferably 8g / water 100g. By setting the solubility in water to be equal to or less than the above upper limit, the acid scavenger can be suppressed from eluting when the polarizing film is produced by stretching the PVA film in a treatment liquid.
[0063] The molecular weight of the acid scavenger is not particularly limited. For example, an acid scavenger with a molecular weight of more than 100 or more than 200 can be used, and the acid scavenger is preferably a polymer. When the PVA film is subjected to swelling treatment, dyeing treatment, stretching treatment, etc. in the treatment solution to manufacture the polarizing film, it is preferred that the acid scavenger in the PVA film is difficult to dissolve into the treatment solution. When the acid scavenger is a polymer, the dissolution of the acid scavenger in the treatment solution is suppressed due to the entanglement of the molecular chain of PVA and the molecular chain of the acid scavenger, and a polarizing film that can more fully suppress the decrease in the light transmittance of the polarizing plate in the high-temperature durability test can be obtained. As described above, from the viewpoint of the polarization performance of the resulting polarizing film, it is preferred to use a water-soluble acid scavenger that is compatible with PVA. However, a water-soluble acid scavenger, especially when the molecular weight is low, is easily dissolved in the treatment solution as an aqueous solution. Therefore, by using a water-soluble and polymeric acid scavenger, a polarizing film with good polarization performance and capable of more fully suppressing the decrease in the light transmittance of the polarizing plate in the high-temperature durability test can be manufactured.
[0064] It should be noted that "polymer" refers to a molecule having a weight average molecular weight of 300 or more, and the weight average molecular weight is preferably 1,000 or more, and more preferably 3,000 or more. On the other hand, the upper limit of the weight average molecular weight of the acid scavenger belonging to the polymer may be, for example, 100,000 or 10,000. Commercially available products of the acid scavenger belonging to the polymer include, for example, the Epicros series manufactured by Nippon Shokubai Co., Ltd., and the Carbodiline series manufactured by Nisshinbo Chemical Co., Ltd., which are water-soluble polycarbodiimide resins.
[0065] As the lower limit of the content of the acid scavenger in the PVA film, relative to 100 parts by mass of PVA, it is preferably 0.1 parts by mass, more preferably 0.5 parts by mass, further preferably 2 parts by mass, and further preferably 5 parts by mass. By setting the content of the acid scavenger to be above the above lower limit, a polarizing film that can improve the acid capture ability, exert a sufficient polyene inhibition function in a high temperature durability test, and more fully inhibit the decrease in the light transmittance of the polarizing plate can be manufactured. On the other hand, as the upper limit of the content, it is preferably 40 parts by mass, more preferably 20 parts by mass, and further preferably 15 parts by mass. By setting the content of the acid scavenger to be below the above upper limit, the film surface is good, and the polarization performance of the resulting polarizing film can be improved.
[0066] (Plasticizer)
[0067] The PVA film may contain a plasticizer. By making the PVA film contain a plasticizer, it is possible to achieve an improvement in the handling and stretchability of the PVA film. As a plasticizer, it is preferred to use a polyol, and as a specific example, ethylene glycol, glycerol, propylene glycol, diethylene glycol, diglycerol, triethylene glycol, tetraethylene glycol, trimethylolpropane, etc. can be listed. The PVA film may contain one or more of these plasticizers. Among these, glycerol is preferably used from the aspect that the stretchability of the PVA film is better.
[0068] The lower limit of the content of the plasticizer in the PVA film is preferably 2 parts by mass, more preferably 3 parts by mass, and further preferably 4 parts by mass relative to 100 parts by mass of PVA. On the other hand, the upper limit of the content is preferably 20 parts by mass, more preferably 17 parts by mass, and further preferably 14 parts by mass relative to 100 parts by mass of PVA. By making the content of the plasticizer in the PVA film more than 2 parts by mass relative to 100 parts by mass of PVA, the stretchability of the PVA film is improved. On the other hand, by making the content of the plasticizer in the PVA film less than 20 parts by mass relative to 100 parts by mass of PVA, it is possible to suppress the plasticizer from seeping out of the surface of the PVA film and suppress the reduction of the handleability of the PVA film.
[0069] (Surfactant)
[0070] The PVA film may contain a surfactant. When the PVA film is manufactured using a film-making stock solution as described later, the film-making property is improved by mixing a surfactant into the film-making stock solution, and the uneven thickness of the film is suppressed. When metal rollers and belts are used in the film-making, the PVA film is easily peeled off from these metal rollers and belts. When the PVA film is manufactured from a film-making stock solution mixed with a surfactant, the PVA film can contain a surfactant. The types of surfactants mixed into the film-making stock solution for manufacturing the PVA film and the surfactants contained in the PVA film are not particularly limited. From the viewpoint of peelability from metal rollers and belts, anionic surfactants and nonionic surfactants are preferably used, and nonionic surfactants are particularly preferably used. One surfactant may be used alone, or two or more surfactants may be used in combination.
[0071] Examples of the anionic surfactant include carboxylic acid type surfactants such as potassium laurate; sulfate ester type surfactants such as octyl sulfate; and sulfonic acid type surfactants such as dodecylbenzenesulfonate.
[0072] Examples of the nonionic surfactant include alkyl ether types such as polyoxyethylene oleyl ether; alkyl phenyl ether types such as polyoxyethylene octylphenyl ether; alkyl ester types such as polyoxyethylene laurate; alkyl amine types such as polyoxyethylene lauryl amino ether; alkyl amide types such as polyoxyethylene lauric acid amide; polypropylene glycol ether types such as polyoxyethylene polyoxypropylene ether; alkanolamide types such as lauric acid diethanolamide and oleic acid diethanolamide; allyl phenyl ether types such as polyoxyalkylene allyl phenyl ether, and the like.
[0073] When a surfactant is added to the film-making stock solution for manufacturing a PVA film, the lower limit of the content of the surfactant in the film-making stock solution and the content of the surfactant in the PVA film is preferably 0.01 mass parts, more preferably 0.02 mass parts, relative to 100 mass parts of PVA contained in the film-making stock solution or the PVA film. On the other hand, the upper limit of the content of the surfactant in the film-making stock solution and the content of the surfactant in the PVA film is preferably 0.5 mass parts, more preferably 0.1 mass parts, relative to 100 mass parts of PVA contained in the film-making stock solution or the PVA film. By making the content of the surfactant more than 0.01 mass parts relative to 100 mass parts of PVA, the film-making property and the peeling property can be improved. On the other hand, by making the content of the surfactant less than 0.5 mass parts relative to 100 mass parts of PVA, it is possible to suppress the surfactant from seeping out to the surface of the PVA film and causing adhesion, and suppress the reduction of handling properties.
[0074] (Other ingredients, etc.)
[0075] The PVA film may contain antioxidants, antifreeze agents, pH adjusters, shielding agents, anti-coloring agents, oils and other ingredients other than the above-mentioned PVA, acid scavengers, plasticizers and surfactants as needed. Among them, the content of other ingredients in the PVA film except PVA, acid scavengers, plasticizers and surfactants is sometimes preferably 1% by mass or less, and sometimes more preferably 0.1% by mass or less. In addition, the content of inorganic compounds in the PVA film is sometimes preferably 1% by mass or less, and preferably 0.1% by mass or less. The above-mentioned other ingredients and inorganic compounds may sometimes cause defects such as pores in the resulting polarizing film. Therefore, by reducing the content of the above-mentioned other ingredients and inorganic compounds, there is a tendency for the polarization performance of the resulting polarizing film to be improved.
[0076] In addition, the PVA film preferably does not contain a component having a large absorption at a wavelength of 210 nm except for PVA and an acid scavenger. Thus, the content of other components except PVA, an acid scavenger, a plasticizer and a surfactant in the PVA film is sometimes preferably less than 1% by mass, and sometimes more preferably less than 0.1% by mass.
[0077] The upper limit of the average thickness D1 of the PVA film is not particularly limited, and is, for example, 100 μm, preferably 80 μm, more preferably 60 μm, and further preferably 40 μm. On the other hand, the lower limit of the average thickness D1 is preferably 5 μm, more preferably 10 μm, and further preferably 15 μm. By making the average thickness of the PVA film within the above range, the handling properties can be improved.
[0078] The shape of the PVA film is not particularly limited. From the perspective of being able to continuously manufacture polarizing films with good productivity, a long film is preferably used. The length of the long film is not particularly limited, and can be appropriately set according to the purpose of the manufactured polarizing film, and can be set, for example, in the range of 5 to 20,000 m. The width of the long film is not particularly limited, and can be set, for example, to be more than 50 cm. From the perspective of seeking wide-width polarizing films in recent years, it is preferably more than 1 m, more preferably more than 2 m, and further preferably more than 4 m. The upper limit of the width of the long film is not particularly limited. If the width is too wide, when using a practical device to manufacture a polarizing film, there is a tendency to be difficult to stretch evenly. Therefore, the width of the PVA film is preferably less than 7 m.
[0079] The shape of the PVA film is not particularly limited, and it can be a single-layer film or a multi-layer film (laminated body). From the perspective of complexity / cost of lamination (coating, etc.) operations, a single-layer film is preferred. The PVA film can be a stretched film or a non-stretched film, preferably a non-stretched film. The unstretched PVA film can be suitably used as a raw material film for the polarizing film described later.
[0080] The polarizing film obtained by using the PVA film can fully suppress the decrease of the light transmittance of the polarizing plate in the high temperature durability test, and therefore, can be suitably used for manufacturing the polarizing plate, and more specifically, can be suitably used for the polarizing film of the polarizing plate. The PVA film can be used as other optical films such as phase difference films, agricultural films, packaging films, etc.
[0081] (Other Implementations)
[0082] The PVA film described in other embodiments of the present invention is a PVA film comprising PVA and an acid scavenger, wherein the content of the acid scavenger is 0.1 parts by mass or more relative to 100 parts by mass of the PVA. The PVA film is the same as the PVA film described in the above embodiment, except that it does not necessarily contain 0.1 parts by mass or more of the acid scavenger relative to 100 parts by mass of the PVA, and the absorbance A1 at a wavelength of 210 nm and the average thickness D1 (mm) satisfy the above formula (1). The specific methods and suitable methods of the PVA film described in other embodiments can apply the description of the PVA film described in the above embodiment.
[0083] (Manufacturing method of PVA film)
[0084] The method for manufacturing the PVA film of the present invention is not particularly limited, and a manufacturing method that makes the thickness and width of the film after film formation more uniform can be preferably adopted. For example, the following film-making stock solution can be used for manufacturing: a film-making stock solution obtained by dissolving the above-mentioned PVA, an acid scavenger, and one or more of the plasticizers, surfactants, and other components that constitute the PVA film into a liquid medium; a film-making stock solution containing PVA, an acid scavenger, and one or more of the plasticizers, surfactants, other components, and liquid medium that are further contained as needed, and the PVA is melted. The method for adding an acid scavenger to the film-making stock solution is not particularly limited, and the acid scavenger can be added together with the PVA and then dissolved or melted, or the acid scavenger can be added after the PVA is dissolved or melted. When the film-making stock solution contains at least one of the acid scavenger, plasticizer, surfactant, and other components, it is preferred that these components are uniformly mixed.
[0085] Examples of the liquid medium used for preparing the membrane-forming stock solution include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, glycerol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, ethylenediamine, diethylenetriamine, etc. Among these, water is preferred from the viewpoint of low environmental burden and recyclability.
[0086] The volatile fraction of the film-forming stock solution (the proportion of volatile components such as liquid medium removed by volatilization and evaporation during film-forming) also varies depending on the film-forming method, film-forming conditions, etc., and as its lower limit, it is preferably 50% by mass, more preferably 55% by mass, and further preferably 60% by mass. On the other hand, as its upper limit, it is preferably 95% by mass, more preferably 90% by mass, and further preferably 85% by mass. By making the volatile fraction of the film-forming stock solution 50% or more by mass, the viscosity of the film-forming stock solution will not be too high, and filtering and degassing will be smoothly performed when preparing the film-forming stock solution, and it is easy to manufacture a PVA film with few foreign matter and defects. On the other hand, by making the volatile fraction of the film-forming stock solution 95% or less by mass, the concentration of the film-forming stock solution will not be too low, and the manufacture of industrial-scale PVA films becomes easy.
[0087] As the film-making method when using the above-mentioned film-making stock solution to manufacture the PVA film, for example, cast film-making method, extrusion film-making method, wet film-making method, gel film-making method, etc. can be listed, preferably cast film-making method and extrusion film-making method. Among them, from the aspect of obtaining a PVA film with uniform thickness and width and good physical properties, extrusion film-making method is more preferred. The PVA film can be dried and heat-treated as needed.
[0088] The heat treatment temperature is not particularly limited and can be appropriately adjusted according to the swelling degree of the PVA film in each range. If the heat treatment temperature is too high, discoloration and degradation of the PVA film are observed, so it is preferably 200°C or less, more preferably 180°C or less, and further preferably 150°C or less. The lower limit of the heat treatment temperature can be set to, for example, 80°C.
[0089] The heat treatment time is not particularly limited and may be appropriately adjusted according to the swelling degree of the PVA film, but is preferably 1 to 60 minutes, more preferably 2 to 40 minutes, and even more preferably 3 to 30 minutes from the viewpoint of efficiently producing the PVA film of the present invention.
[0090] <Polarizing Film>
[0091] The polarizing film described in one embodiment of the present invention is a polarizing film formed by the PVA film of the present invention. The polarizing film is usually formed by adsorbing a dichroic pigment such as an iodine pigment or a dichroic organic dye on a stretched film obtained by uniaxially stretching a non-stretched PVA film of one embodiment of the present invention to orient it.
[0092] The polarizing film described in other embodiments of the present invention is a polarizing film containing PVA, and the absorbance A2 and the average thickness D2 (mm) at a wavelength of 210 nm after standing for 100 hours at 60°C and 90% RH atmosphere satisfy the following formula (3). It should be noted that by standing for 100 hours at 60°C and 90% RH atmosphere, dichroic pigments such as iodine-based pigments are volatilized to form a substantially transparent film. Therefore, by measuring the absorbance after standing for 100 hours at 60°C and 90% RH atmosphere, the presence of groups that can capture acids and have absorption at a wavelength of 210 nm and the degree of their content can be confirmed. In addition, the unit of A2 / D2 is mm -1 .
[0093] A2 / D2≥9 ・・・(3)
[0094] Regarding the relationship between the absorbance A2 and the average thickness D2, the lower limit of A2 / D2 is preferably 10 mm. -1 , more preferably 12 mm -1 , more preferably 14 mm -1 , and more preferably 20 mm -1 , particularly preferably 25 mm -1 By setting A2 / D2 to be above the above lower limit, a polarizing film is formed that can further improve the acid capture ability, fully suppress polyene formation in a high-temperature durability test, and more fully suppress the decrease in light transmittance of the polarizing plate. On the other hand, the upper limit of A2 / D2 can be, for example, 100 mm -1 , preferably 80mm -1 , more preferably 50 mm -1 By setting A2 / D2 to be below the above upper limit, the film surface is good and the polarization performance of the polarizing film can be improved.
[0095] The polarizing film according to another embodiment of the present invention may be a film obtained by adsorbing a dichroic dye such as an iodine-based dye or a dichroic organic dye onto a stretched film obtained by uniaxially stretching and orienting a non-stretched PVA film, which is one embodiment of the present invention.
[0096] The upper limit of the average thickness D2 of the polarizing film of the present invention is, for example, 100 μm, preferably 50 μm, and more preferably 30 μm. On the other hand, the lower limit of the average thickness may be 1 μm, and preferably 5 μm.
[0097] (Method for producing polarizing film)
[0098] The method for manufacturing the polarizing film of the present invention is not particularly limited, and any method that has been used so far can be used. For example, the polarizing film can be manufactured by subjecting the PVA film of the present invention to swelling treatment, dyeing treatment, uniaxial stretching, and further subjecting the PVA film to crosslinking treatment, fixing treatment, drying treatment, heat treatment, etc. as needed. At this time, the order of each treatment such as swelling treatment, dyeing treatment, uniaxial stretching, fixing treatment, etc. is not particularly limited, and one or more treatments can be performed simultaneously. In addition, one or more of each treatment can be performed twice or more.
[0099] The swelling treatment can be performed by immersing the PVA film in water. The lower limit of the temperature of the water during immersion in water is preferably 20°C, more preferably 22°C, and further preferably 25°C. On the other hand, the upper limit is preferably 40°C, more preferably 38°C, and further preferably 35°C. In addition, the immersion time in water is preferably, for example, 0.1 to 5 minutes. It should be noted that the water during immersion in water is not limited to pure water, and may be an aqueous solution in which various components are dissolved, or may be a mixture of water and an aqueous medium.
[0100] The dyeing treatment can be carried out using dichroic pigments such as iodine-based pigments and dyes. The dyeing period can be any stage before uniaxial stretching, during uniaxial stretching, and after uniaxial stretching. Dyeing is generally carried out by immersing the PVA film in a solution (especially an aqueous solution) containing iodine-potassium iodide as a dyeing bath. The iodine concentration in the dyeing bath is preferably 0.01 to 0.5% by mass, and the concentration of potassium iodide is preferably 0.01 to 10% by mass. In addition, the temperature of the dyeing bath is preferably set to 20 to 60°C.
[0101] The cross-linking treatment can be carried out by immersing the PVA film in an aqueous solution containing a cross-linking agent. If the cross-linking treatment is carried out, cross-linking is introduced into the PVA film, and uniaxial stretching can be performed at a higher temperature. As the cross-linking agent used, one or more boron compounds such as borate such as boric acid and borax can be used. The concentration of the cross-linking agent in the aqueous solution containing the cross-linking agent is preferably 1 to 15% by mass, more preferably 2 to 7% by mass. The temperature of the aqueous solution containing the cross-linking agent is preferably 20 to 60°C.
[0102] The uniaxial stretching can be performed by either a wet stretching method or a dry stretching method. In the case of the wet stretching method, it can be performed in an aqueous solution containing boric acid, or in the above-mentioned dyeing bath or the fixing treatment bath described later. In addition, in the case of the dry stretching method, it can be performed in the air. Among these, the wet stretching method is preferably used, and the uniaxial stretching is more preferably performed in an aqueous solution containing boric acid. The boric acid concentration in the boric acid aqueous solution is preferably 0.5 to 6.0% by mass, more preferably 1.0 to 5.0% by mass, and further preferably 1.5 to 4.0% by mass. In addition, the boric acid aqueous solution may contain potassium iodide, and its concentration is preferably 0.01 to 10% by mass.
[0103] In the wet stretching method, the stretching temperature in the uniaxial stretching is preferably 30 to 90°C, more preferably 40 to 80°C, and further preferably 50 to 70°C.
[0104] From the viewpoint of polarization performance of the obtained polarizing film, the stretching ratio in uniaxial stretching is preferably 5 times or more, more preferably 5.5 times or more. The upper limit of the stretching ratio is not particularly limited, but the stretching ratio is preferably 8 times or less.
[0105] When manufacturing a polarizing film, in order to make the dichroic pigment firmly adsorbed to the PVA film, it is preferred to perform a fixing treatment. As a fixing treatment bath used in the fixing treatment, an aqueous solution containing one or more boron compounds such as boric acid and borax can be used. In addition, iodine compounds and metal compounds can also be added to the fixing treatment bath as needed. The concentration of the boron compound in the fixing treatment bath is generally preferably about 2 to 15% by mass, particularly preferably about 3 to 10% by mass. The temperature of the fixing treatment bath is preferably 15 to 60°C, particularly preferably 25 to 40°C.
[0106] The drying treatment is preferably performed at 30 to 150° C., and more preferably at 50 to 130° C. By drying at a temperature within the above range, a polarizing film having excellent dimensional stability can be easily obtained.
[0107] <Polarizing Plate>
[0108] The polarizing plate of the present invention comprises the polarizing film of the present invention and a protective film made of a cellulose ester-based resin. The polarizing plate according to one embodiment of the present invention comprises, for example, a protective film laminated on at least one surface of the polarizing film via an adhesive.
[0109] The protective film is usually a cellulose ester film containing a cellulose ester resin as a main component. The content of the cellulose ester resin in the protective film is preferably 70% by mass or more, and more preferably 90% by mass or more. Examples of the cellulose ester resin include cellulose triacetate (triacetyl cellulose: TAC), cellulose diacetate, cellulose acetate propionate, cellulose acetate butyrate, cellulose acetate benzoate, cellulose acetate propionate benzoate, cellulose propionate, cellulose butyrate, biphenyl cellulose acetate, and biphenyl cellulose acetate propionate. Among these, cellulose triacetate is preferred.
[0110] Generally, when a polarizing plate using a protective film containing a cellulose ester resin is exposed to high temperature for a long time, the cellulose ester in the protective film is hydrolyzed to generate an acid that promotes polyene formation of the polarizing film. In contrast, the present polarizing plate can suppress polyene formation because the polarizing film can capture the acid, thereby suppressing the decrease in light transmittance.
[0111] As the adhesive for bonding the polarizing film to the protective film, PVA-based adhesives, ultraviolet curing adhesives, etc. can be listed, among which PVA-based adhesives are suitable. The PVA-based adhesive can also contain an acid scavenger. As the PVA-based adhesive, an aqueous solution of PVA can be used. Example
[0112] The present invention is specifically described by the following examples, but the present invention is not limited to these examples at all. It should be noted that the evaluation methods used in the following examples and comparative examples are as follows.
[0113] [Measurement of Swelling Degree of PVA Film]
[0114] Take about 1.5g of PVA film and cut it into about 2mm×10cm. Then, wrap the cut PVA film with a mesh ("N-N0110S 115" manufactured by NBC Meshtech) and immerse it in distilled water at 30°C for 15 minutes. Next, the PVA film wrapped with the mesh is centrifuged at 3,000rpm for 5 minutes, and after removing the mesh, the mass (W1) of the PVA film is calculated. Next, the PVA film is dried in a dryer at 105°C for 16 hours, and the mass (W2) is calculated. In addition, the swelling degree of the PVA film is calculated by the following formula.
[0115] Swelling degree (%) = {(W1) / (W2)}×100.
[0116] [Measurement of absorbance A1]
[0117] The PVA film was cut into 4 cm squares, and the absorbance in the wavelength range of 200 to 780 nm was measured using a spectrophotometer ("U-4100" manufactured by Hitachi High-Tech Science & Technology Co., Ltd.), and the absorbance A1 at a wavelength of 210 nm was determined.
[0118] [Measurement of absorbance A2]
[0119] The polarizing film was cut into 4 cm squares and fixed to a metal frame, and then left to stand for 100 hours in a constant temperature and humidity chamber set at 60°C and 90% RH to obtain a transparent film. Thereafter, the absorbance of the transparent film in the wavelength range of 200 to 780 nm was measured using a spectrophotometer ("U-4100" manufactured by Hitachi High-Tech Science & Technology Co., Ltd.), and the absorbance A2 at a wavelength of 210 nm was obtained.
[0120] [Measurement of average thickness D1 and D2]
[0121] The average thickness D1 of the PVA film and the average thickness D2 of the polarizing film were measured using a contact thickness meter (linear measurement sensor “GS-3813” manufactured by Ono Sokki Co., Ltd.).
[0122] [Polarization performance]
[0123] (a) Measurement of light transmittance Ts
[0124] Take two square samples of 3 cm in length and 2 cm in width from the polarizing film. According to JIS Z8722:2009 (method for measuring object color), use a spectrophotometer with an integrating sphere ("V7100" manufactured by JASCO Corporation) to measure the light transmittance at a tilt of 45° relative to the length direction and the light transmittance at a tilt of -45° for one sample, and calculate their average value Ts1 (%). It should be noted that the measurement is carried out by performing visibility correction in the visible light region with a C light source and a 2° field of view. The same operation is performed on the other sample, and the light transmittance at a tilt of 45° and the light transmittance at a tilt of -45° are measured, and their average value Ts2 (%) is calculated. The average value of Ts1 and Ts2 is taken as the light transmittance Ts (%) of the polarizing film.
[0125] In the following measurement of the polarization degree V, the dyeing treatment conditions were adjusted so that the light transmittance Ts became 44.0%, and a sample was prepared, and the polarization degree was measured.
[0126] (b) Determination of polarization degree V
[0127] The two samples taken in the measurement of the light transmittance Ts are overlapped so that their length directions are parallel, and the light transmittance when tilted 45° and -45° relative to the length direction is measured, and their average value T∥ (%) is obtained. Next, the two samples are overlapped so that their length directions are orthogonal, and the light transmittance when tilted 45° and -45° relative to the length direction is measured, and their average value T⊥ (%) is obtained, and the polarization degree V (%) is obtained by the following formula.
[0128] V={(T∥-T⊥) / (T∥+T⊥)} 1 / 2 ×100.
[0129] Polarization performance was determined according to the following criteria based on the obtained polarization degree V. Note that A, B, and C were judged to be good because they could be used in practice without any problem, and D was judged to be poor.
[0130] A: When the transmittance Ts is 44.0%, the polarization degree V is 99.0% or more
[0131] B: When the transmittance Ts is 44.0%, the polarization degree V is 95.0% or more and less than 99.0%
[0132] C: When the transmittance Ts is 44.0%, the polarization degree V is 90.0% or more and less than 95.0%
[0133] D: When the transmittance Ts is 44.0%, the polarization degree V is less than 90.0%.
[0134] [High temperature durability test]
[0135] (a) Sample preparation
[0136] The polarizing plate was cut into 4 cm squares, and a 10 cm square glass plate (1 mm thick) and an adhesive sheet ("MCS70" manufactured by Meikan Imazing Co., Ltd.; thickness 25 μm) cut into 10 cm squares were used. The glass plate / adhesive sheet / polarizing plate / adhesive sheet / glass plate were stacked in the order of laminating and pressed using a laminator. At this time, the polarizing plate was stacked on the center of the glass plate. Thereafter, a vacuum laminator ("1522N" manufactured by Nisshinbo Metalonics Co., Ltd.) was used to apply a pressure of 10 kPa at 50 ° C for 5 minutes, and further pressed. It should be noted that the light transmittance of the obtained high temperature durability test sample measured by the light transmittance measurement method described later is in the range of 35 to 40%.
[0137] (b) High temperature durability test
[0138] The prepared high temperature durability test sample was placed in a 105°C dryer for 250 hours. Thereafter, the light transmittance of the sample was measured by the method described below. Furthermore, the sample was placed in a 115°C dryer for 70 hours. Thereafter, the light transmittance of the sample taken out was measured by the method described below.
[0139] (c) Determination of light transmittance
[0140] The light transmittance at the center of the high temperature durability test sample when tilted 45° and -45° relative to the absorption axis direction of the polarizing film was measured using a spectrophotometer with an integrating sphere ("U4100" manufactured by Hitachi High-Tech Science & Technology Co., Ltd.), and their average value T (%) was determined.
[0141] High temperature durability was determined according to the following criteria: A, B, and C were judged to be good because they could be used in practice without any problems, and D was judged to be poor.
[0142] A: The light transmittance after high temperature durability test is more than 20%
[0143] B: The light transmittance after high temperature durability test is 10% or more and less than 20%
[0144] C: The light transmittance after high temperature durability test is 1% or more and less than 10%
[0145] D: The light transmittance after the high-temperature durability test is less than 1%.
[0146] The acid scavengers used in Examples and Comparative Examples are shown below.
[0147] Acid scavenger A: a high molecular weight (molecular weight of about 1,000 to 5,000) carbodiimide compound, namely "Carbodiimide V-04" (manufactured by Nisshinbo Chemical Co., Ltd., solubility 5 g / 100 g water, carbodiimide group equivalent 339 g / mol)
[0148] Acid scavenger B: a high molecular weight (molecular weight of about 1,000 to 5,000) carbodiimide compound, namely "Carbodiimide V-02" (manufactured by Nisshinbo Chemical Co., Ltd., solubility 100 g / 100 g water, carbodiimide group equivalent 602 g / mol)
[0149] Acid scavenger C: a high molecular weight (molecular weight of about 1,000 to 5,000) carbodiimide compound, namely "Carbodiimide SV-02" (manufactured by Nisshinbo Chemical Co., Ltd., solubility 100 g / 100 g water, carbodiimide group equivalent 429 g / mol)
[0150] Acid scavenger D: N,N'-dicyclohexylcarbodiimide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., solubility less than 1g / 100g water)
[0151] Acid scavenger E: 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., solubility: 10 g / 100 g water).
[0152] [Example 1]
[0153] (1) Manufacturing of PVA film
[0154] PVA (a saponified product of a homopolymer of vinyl acetate, the polymerization degree of PVA is 2,400, and the saponification degree of PVA is 99.95 mol%), glycerol (10 parts by mass relative to 100 parts by mass of PVA), a surfactant (0.03 parts by mass relative to 100 parts by mass of PVA) and water were mixed and dissolved at 90°C for 4 hours to obtain a PVA aqueous solution. Thereafter, as an acid scavenger, 10 parts by mass of an acid scavenger A was added relative to 100 parts by mass of PVA, and stirred at 85°C for 30 minutes. It should be noted that the amount of acid scavenger added in Table 1 represents the solid content (parts by mass) of the acid scavenger relative to 100 parts by mass of PVA, which is equal to the content in the obtained PVA film. Thereafter, in order to degas the PVA aqueous solution, the PVA aqueous solution was kept at 85°C for 16 hours.
[0155] The obtained PVA aqueous solution was dried on a metal roll at 80° C., and the obtained film was heat-treated in a dryer at 110° C. for 10 minutes to obtain a PVA film (average thickness: 30 μm) having a swelling degree of 200%.
[0156] The absorbance A1 and the average thickness D1 of the obtained PVA film were measured according to the above method, and their ratio A1 / D1 was calculated. The results are shown in Table 1. Figure 1 ] The absorption spectrum of the obtained PVA film in the wavelength range of 200 to 400 nm is shown in FIG.
[0157] (2) Manufacturing of polarizing films
[0158] A test piece of 9 cm in length direction and 10 cm in width direction was taken from the obtained PVA film. Both ends of the test piece in the length direction were fixed to a stretching tool in such a way that the size of the stretched part became 5 cm in length direction and 10 cm in width direction, and the test piece was immersed in water at a temperature of 30°C for 38 seconds, and then uniaxially stretched (first stage stretching) along the length direction to 2.2 times the original length at a stretching speed of 24 cm / min. Thereafter, the test piece was immersed in an iodine / potassium iodide aqueous solution at a temperature of 30°C containing iodine at a concentration of 0.03% by mass and potassium iodide at a concentration of 3% by mass for 60 seconds, and then uniaxially stretched (second stage stretching) along the length direction to 3.3 times the original length at a stretching speed of 24 cm / min. Next, the test piece was immersed in a boric acid / potassium iodide aqueous solution at a temperature of 30°C containing 3% by mass of boric acid and 3% by mass of potassium iodide for about 20 seconds, and then uniaxially stretched (third stage stretching) in the longitudinal direction to 3.6 times the original length at a stretching speed of 24 cm / min. Next, the test piece was immersed in a boric acid / potassium iodide aqueous solution at a temperature of 58°C containing 4% by mass of boric acid and about 5% by mass of potassium iodide, and then uniaxially stretched (fourth stage stretching) in the longitudinal direction to 5.5 times the original length at a stretching speed of 24 cm / min. Thereafter, the test piece was immersed in a potassium iodide aqueous solution containing 1.5% by mass of boric acid and 3% by mass of potassium iodide for 10 seconds to perform a fixing treatment, and then dried in a dryer at 60°C for 4 minutes to obtain a polarizing film (average thickness of 13 μm).
[0159] The absorbance A2 and the average thickness D2 of the obtained polarizing film were measured by the above method, and their ratio A2 / D2 was calculated. In addition, the polarization performance was evaluated by the above method. The results are shown in Table 1.
[0160] (3) Manufacturing of polarizing plates
[0161] A test piece of 10 cm in length and 5 cm in width was taken from the obtained polarizing film. A triacetyl cellulose film was attached to both sides of the test piece (polarizing film) using a PVA-based adhesive (a 3.5% by mass aqueous solution of PVA), and dried at 60°C for 10 minutes to produce a polarizing plate. It should be noted that the PVA in the PVA-based adhesive used is a saponified homopolymer of vinyl acetate, the degree of polymerization of PVA is 2,400, and the degree of saponification of PVA is 99.95 mol%.
[0162] Using the polarizing plate, a high temperature durability test was carried out according to the above method to evaluate the light transmittance. The results are shown in Table 1.
[0163] [Example 2]
[0164] A PVA film, a polarizing film, and a polarizing plate were manufactured in the same manner as in Example 1 except that the acid scavenger B was used as the acid scavenger. Various evaluations were performed on them in the same manner as in Example 1. The results are shown in Table 1. Figure 1 ] The absorption spectrum of the obtained PVA film in the wavelength range of 200 to 400 nm is shown in FIG.
[0165] [Example 3]
[0166] A PVA film, a polarizing film, and a polarizing plate were manufactured in the same manner as in Example 1 except that the acid scavenger C was used as the acid scavenger. Various evaluations were performed on them in the same manner as in Example 1. The results are shown in Table 1. Figure 1 ] The absorption spectrum of the obtained PVA film in the wavelength range of 200 to 400 nm is shown in FIG.
[0167] [Example 4]
[0168] A PVA film, a polarizing film, and a polarizing plate were manufactured in the same manner as in Example 1 except that the content (addition amount) of the acid scavenger A was set to 1 part by mass relative to 100 parts by mass of PVA. Various evaluations were performed on them in the same manner as in Example 1. However, a high temperature durability test at 115° C. for 70 hours was not performed. The results are shown in Table 1.
[0169] [Example 5]
[0170] The same operation as in Example 1 was performed except that the content (addition amount) of the acid scavenger A was set to 30 parts by mass relative to 100 parts by mass of PVA, to manufacture a PVA film, a polarizing film, and a polarizing plate. In the same manner as in Example 1, various evaluations were performed on them. Among them, a high-temperature durability test at 115°C for 70 hours was not performed. The results are shown in Table 1. It should be noted that due to the excessive addition of the acid scavenger, the film surface of the obtained PVA film and the polarizing film was poor.
[0171] [Example 6]
[0172] A PVA film, a polarizing film and a polarizing plate were manufactured in the same manner as in Example 1 except that the acid scavenger D was used as the acid scavenger. Various evaluations were performed on them in the same manner as in Example 1. Among them, a high temperature durability test at 115°C for 70 hours was not performed. The results are shown in Table 1. It should be noted that the acid scavenger D is not water-soluble and has poor compatibility with PVA. Therefore, the film surfaces of the obtained PVA film and polarizing film are poor.
[0173] [Example 7]
[0174] A PVA film, a polarizing film, and a polarizing plate were manufactured in the same manner as in Example 1 except that the acid scavenger E was used as the acid scavenger. Various evaluations were performed on them in the same manner as in Example 1. However, the high-temperature durability test at 115°C for 70 hours was not performed. The results are shown in Table 1. It should be noted that the acid scavenger E has a small molecular weight and is easily dissolved in the polarizing film manufacturing process. Therefore, the amount of the carbodiimide compound remaining in the polarizing film is reduced, and the value of A2 / D2 is small.
[0175] [Comparative Example 1]
[0176] A PVA film, a polarizing film, and a polarizing plate were produced in the same manner as in Example 1 except that no acid scavenger was added. Various evaluations were performed on these in the same manner as in Example 1. The results are shown in Table 1. Figure 1 ] The absorption spectrum of the obtained PVA film in the wavelength range of 200 to 400 nm is shown in FIG.
[0177] [Comparative Example 2]
[0178] A PVA film, a polarizing film, and a polarizing plate were produced in the same manner as in Example 1 except that the content (addition amount) of the acid scavenger A was 0.01 parts by mass relative to 100 parts by mass of PVA. Various evaluations were performed on these in the same manner as in Example 1. The results are shown in Table 1.
[0179]
[0180] like Figure 1 As shown in Table 1, the PVA films of Examples 1 to 3 to which an acid scavenger having a group capable of scavenging acid, namely a carbodiimide group, was added exhibited large absorption near a wavelength of 210 nm. -1 The decrease in light transmittance of the polarizing plates of the polarizing films obtained from the PVA films of the above Examples 1 to 7 in the high-temperature durability test (105°C, 250h) is fully suppressed. It should be noted that in Example 5 in which the amount of acid scavenger added is large and in Example 6 in which a water-insoluble acid scavenger is used, the polarization performance of the obtained polarizing film is slightly lower due to the deterioration of the film surface. In addition, in Example 4 in which the amount of acid scavenger added is small and in Example 7 in which a low molecular weight acid scavenger is used, the residual amount of acid scavenger in the obtained polarizing film is reduced, and the high-temperature durability is slightly lower. According to the results of the high-temperature durability test (105°C, 250°C + 115°C, 70h), when comparing Examples 1 to 3, it can be seen that as the value of A2 / D2 increases, the high-temperature durability is further improved.
[0181] Industrial Applicability
[0182] The PVA film of the present invention can be suitably used as a raw material film of a polarizing film used in a polarizing plate, etc.
Claims
1. A polyvinyl alcohol film comprising polyvinyl alcohol, an acid scavenger, a plasticizer and a surfactant, The acid scavenger is a carbodiimide compound having at least one carbodiimide group. The content of the acid scavenger is 0.1 parts by mass or more relative to 100 parts by mass of the polyvinyl alcohol. The content of other components except the above-mentioned polyvinyl alcohol, acid scavenger, plasticizer and surfactant is 1% by mass or less, and the absorbance A1 and average thickness D1 of the polyvinyl alcohol film at a wavelength of 210nm satisfy the following formula (1), and the unit of the average thickness D1 is mm, A1 / D1≥10· · · (1).
2. The polyvinyl alcohol film according to claim 1, wherein The absorbance A1 and the average thickness D1 satisfy the following formula (2), and the unit of the average thickness D1 is mm. 10≤A1 / D1≤80···(2).
3. The polyvinyl alcohol film according to claim 1 or 2, wherein The content of the acid scavenger is 0.5 parts by mass or more based on 100 parts by mass of the polyvinyl alcohol.
4. The polyvinyl alcohol film according to claim 1 or 2, wherein The acid scavenger is water-soluble.
5. The polyvinyl alcohol film according to claim 4, wherein The acid scavenger is a polymer.
6. The polyvinyl alcohol film according to claim 1 or 2, wherein The polyvinyl alcohol has a saponification degree of 90 mol% or more. The polyvinyl alcohol film according to claim 1 or 2, which is used for producing a polarizing plate. 8 . A polarizing film comprising the polyvinyl alcohol film according to claim 1 .
9. A polarizing film comprising polyvinyl alcohol, an acid scavenger, a plasticizer and a surfactant, The acid scavenger is a carbodiimide compound having at least one carbodiimide group. The content of the acid scavenger is 0.1 parts by mass or more relative to 100 parts by mass of the polyvinyl alcohol. The content of other components except the above-mentioned polyvinyl alcohol, acid scavenger, plasticizer and surfactant is less than 1% by mass, and the absorbance A2 and average thickness D2 of the polarizing film at a wavelength of 210nm after standing for 100 hours in an atmosphere of 60°C and 90% RH satisfy the following formula (3), and the unit of the average thickness D2 is mm, A2 / D2≥10 · · · (3). 10 . A polarizing plate comprising the polarizing film according to claim 8 or 9 and a protective film containing a cellulose ester resin.
Citation Information
Patent Citations
Polarizing plate and image display device, and manufacturing method of those
JP2014102353A
Optical laminate
JP2018025764A
Polarizer protection film, polarizing plate and liquid crystal display element
CN101887143A
Resin composition and optical film using same
CN108026346A
Method of manufacturing a polarizing plate, polarizing plate manufactured using said method, and liquid crystal display device
WO2011108350A1
